"O passado é a morte das coisas" - Padre Ibiapina: ante o esquecimento, a memória em construção. - Neves, Gilvan Gomes das (2019)
The objective of this study is to analyze the trajectory and mission of Father Ibiapina (1806-1883) in the Brazilian Northeast, showing why his actions have been forgotten for about a hundred years and a revival of his memory in the present day. As a methodology, the research is characterized as predominantly qualitative, of socio-historical analysis, and the case study was adopted. The study was based on the documentary analysis of the reports of the missions of Father Ibiapina, the Statute and the Rules of Order, which ordered the functioning of the Houses of Charity, in the main biographies, all publications on the subject, of various authors, interested and curious, religious or not that they wrote about the missionary activity of Ibiapina. In addition, interviews were held at the Sanctuary of Santa Fe, Arara - PB, pilgrimage site of the devotees of Father Ibiapina: with the former rector of the Sanctuary, Father Gaspar, with the current rector, Father José Florence, who organized the archive, with two bishops, as well as with the pilgrims who visited the Sanctuary. There was also the contribution of Oral History, which values stories told by ordinary people who previously had no opportunity to be heard. Ibiapina's life trajectory is part of the socioeconomic and cultural reality of the northeastern semi-arid region, with its contradictions that gravitate towards various fields, such as popular Catholicism and its subfields: mystical Catholicism, the sertanejo, which permeate and delineate the same existence. It can be concluded that the inheritance of Father Ibiapina was not directly confronted, questioned. They simply let it die, like a little plant that dies without water ... doing nothing to renew it or give it continuity, a space of survival. For almost a hundred years, Father Ibiapina remained not only unknown, but also relegated, for his example of life pointed to a model that is much more distinct from a pastoral one that has as its background a preferential option for the poor. Only after the emergence of the Basic Ecclesial Communities in the 1970s and the Latin American Episcopal Conference in Puebla in 1979 has there been a new appreciation of the religion of the people or of the Catholic Church. which is still left of her. In the construction of this memory of the Saint of Santa Fe, a number of pastoral agents were discovered: bishops, priests, religious, lay people, about their beautiful example of life, pastoral activity and holiness, and they became promoters of their cause, especially those who passed through the diocese of Guarabira: Dom Marcelo Carvalheira and Dom Antonio Muniz. In the crowd that comes to the Sanctuary of Santa Fe on February 19, not only the recognition of their heroic virtues, of their sanctity, but also an affirmation, a recognition of their missionary way of life, has penetrated the heart and soul. of the Northeastern people.